Platelets in infection: intrinsic roles and functional outcomes - Hu, Yuwei; Dai, Shuchang; Qiao, Congchao; Ye, Yifan; Ren, Junyi; Wang, Kai; Li, Ling; Liu, Zhong (Frontiers in Immunology, 2025)
Platelets have long been acknowledged for their essential roles in hemostasis and thrombosis; however, recent insights highlight their broader involvement as key participants in host responses during infection. Beyond their classical functions, platelets exhibit diverse anti-infective capabilities, such as direct pathogen internalization, receptor-mediated pathogen recognition, the release of antimicrobial peptides, cytokines, and chemokines, and the generation of immunomodulatory extracellular vesicles. These intrinsic platelet attributes enable dynamic interactions with pathogens and immune cells, significantly contributing to pathogen capture, neutralization, and the orchestration of innate and adaptive immune responses. This review examines the multifaceted intrinsic roles of platelets and delineates the beneficial outcomes of their activation, providing an integrated perspective on platelet-driven immunity and defense mechanisms during infection.